2014
DOI: 10.1002/cncr.29081
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1B/2 study of aldoxorubicin in patients with soft tissue sarcoma

Abstract: BACKGROUND: Aldoxorubicin, a prodrug of doxorubicin, covalently binds to serum albumin, allowing for the administration of much higher doses of doxorubicin in a previous clinical study. The current phase 1B/2 study evaluated the safety of aldoxorubicin, including preliminary efficacy and safety of its maximum tolerated dose (MTD RESULTS: A total of 25 patients were enrolled, including 17 patients (68%) with advanced soft tissue sarcoma (STS). The MTD of aldoxorubicin was 350 mg/m 2 ; dose-limiting toxicities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Exendin-4, a GLP-1 homologue (CJC-1131) for treatment of type 2 diabetes, is one example that has entered clinical trials [234][235][236], where the half-life has been shown to be increased from only a few hours for the GLP-1 analogue to 9-15 days for the C34-conjugated drug [237]. Another example of in vivo conjugation is coupling of an acidic sensitive prodrug of doxorubicin (Aldoxorubicin) to C34 post intravenous administration, which is currently in clinical trials for treatment of sarcoma [238]. This strategy aims for cleavage of the hydrazine linker connecting albumin and doxorubicin upon exposure to the acidic environment in tumor tissues [238].…”
Section: Covalent Conjugation Of Drugs To Albuminmentioning
confidence: 99%
See 1 more Smart Citation
“…Exendin-4, a GLP-1 homologue (CJC-1131) for treatment of type 2 diabetes, is one example that has entered clinical trials [234][235][236], where the half-life has been shown to be increased from only a few hours for the GLP-1 analogue to 9-15 days for the C34-conjugated drug [237]. Another example of in vivo conjugation is coupling of an acidic sensitive prodrug of doxorubicin (Aldoxorubicin) to C34 post intravenous administration, which is currently in clinical trials for treatment of sarcoma [238]. This strategy aims for cleavage of the hydrazine linker connecting albumin and doxorubicin upon exposure to the acidic environment in tumor tissues [238].…”
Section: Covalent Conjugation Of Drugs To Albuminmentioning
confidence: 99%
“…Another example of in vivo conjugation is coupling of an acidic sensitive prodrug of doxorubicin (Aldoxorubicin) to C34 post intravenous administration, which is currently in clinical trials for treatment of sarcoma [238]. This strategy aims for cleavage of the hydrazine linker connecting albumin and doxorubicin upon exposure to the acidic environment in tumor tissues [238]. As FcRn-mediated transport is dependent on binding at acidified endosomal pH, it remains to be investigated whether the acidic-sensitive linker is protected or cleaved.…”
Section: Covalent Conjugation Of Drugs To Albuminmentioning
confidence: 99%
“…The median PFS was 11.25 months and median OS 21.71 months. Of note, five out of the eight patients who demonstrated response had previously been treated with an anthracycline [51]. A subsequent Phase II study randomizing patients to aldoxorubicin or doxorubicin in first-line STS was presented at the American Society of Clinical Oncology annual meeting 2014.…”
Section: Aldoxorubicinmentioning
confidence: 99%
“…The recommended aldoxorubicin dose was determined to be 350 mg/m 2 (260 mg/m 2 doxorubicin dose equivalent). In the Phase Ib portion of the second study, 25 patients with advanced solid tumors, including 17 with STS, received aldoxorubicin at 230, 350 or 450 mg/m 2 once every 21 days for up to eight cycles [45]. The 350 mg/m 2 dose was confirmed as the maximum tolerated dose (MTD).…”
Section: Pharmacokinetics and Metabolism Of Aldoxorubicinmentioning
confidence: 99%
“…Additional patients were enrolled to bring the total to 13 patients with STS treated with aldoxorubicin 350 mg/m 2 [45]. This patient cohort completed a median of six cycles (range 1 --8).…”
Section: Phase II Studiesmentioning
confidence: 99%